THE INFLUENCE OF COMPETENCE, WORK PROFESSIONALISM AND COMMITMENT ON EMPLOYEES PERFORMANCE AT PT ANEKA KARYA BOYOLALI - Iin Nandita Rahmawati; Karnowahadi Karnowahadi; Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2018)
The purpose of this study was to determine (1) the influence of competence on employees performance at PT Aneka Karya Boyolali, (2) the influence of work professionalism on employees performance at PT Aneka Karya Boyolali, (3) the influence of commitment on employees performance at PT Aneka Karya Boyolali, and (4) The influence of competence, work professionalism and commitment on employees performance at PT Aneka Karya Boyolali. Population and sample in this study amounted to 74 respondents who were employees of PT Aneka Karya Boyolali. Data collection techniques are questionnaires, observation and literature study. Methods of analysis using multiple linear regression analysis with the help of SPSS for Windows 22.0 software. From the results of this study, it can be found that competence, work professionalism and commitment influence on employees performance at PT Aneka Karya Boyolali with R square value is 0.847. R square value is 0.847 means the contribution of competence, work professionalism and commitment to employee performance is 84.7% and the remaining 15.3% is influenced by other variables not examined in this study.